How Motivation Works to Promote the Relationship Between Work Environment and Organizational Commitment to the Performance of Dharmasraya District Secretariat - Doli Putra Harahap; Juli Ronaldi; Darman Darman; Yulina Eliza (Universitas Batanghari, 2020)
The purpose of this study was to determine the effect of work environment on employee work motivation, determine the effect of organizational commitment on employee work motivation, know the effect of work environment on employee performance, find out the effect of organizational commitment on employee performance, find out the effect of work motivation on employee performance, know the role work motivation in mediating the relationship between work environment and employee performance and knowing the role of work motivation in mediating the relationship between organizational commitment and employee performance. The object of research is employees in the Regional Secretariat of Dharmasraya Regency with a population of 85 people. The sampling technique is done by non-probability sampling with saturation sampling technique where all members of the population are used so that the number of research samples is 85 people. The type of data used is primary data, the data collection method uses questionnaires with a Likert scale. Test the research instrument to test the validity and reliability. Data analysis techniques consist of test data description, assumption test, path analysis and hypothesis testing. The results of the study found that there was a positive and significant influence of the work environment on work motivation, there was a positive and significant effect on organizational commitment to work motivation, there was a positive and significant effect on the work environment on employee performance, there was a positive and significant effect on organizational commitment to employee performance, there was an influence positive and significant work motivation on employee performance, there is no role of work motivation in mediating the relationship between work environment and employee performance with the value of an indirect influence smaller than its direct influence, there is no role of work motivation in mediating the relationship between organizational commitment and employee performance with the value of the indirect effect is smaller than the direct effect. The results of the study suggest that to improve employee performance, it is expected that an increase in work motivation, a conducive work environment and an increase in organizational commitment.